2018
DOI: 10.1016/j.jor.2018.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic knotless rotator cuff repair: Factors associated with construct selection and recent trends from a manual review of 1617 cases

Abstract: There was a significant increase from 2009 to 2016 in SR knotless and double row medial row knotless constructs contrasting the declining use of the SR knotted technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Surgical data included nature of concomitant procedures (ie, use of allograft, biceps tenodesis, capsular release), American Society of Anesthesiologists score (1 or 2 versus ≥3), number of anchors used, history of prior ipsilateral or contralateral nonarthroscopic shoulder surgery, prior ipsilateral or contralateral arthroscopic shoulder surgery, subsequent upper or lower extremity arthroscopy, and any ipsilateral revision surgery. The number of anchors placed was used as a surrogate for rotator cuff tear size based on the findings of Shah et al 21 Procedures were categorized as primary repair of the rotator cuff with or without decompression/débridement (type 1) versus those with concomitant use of allograft (superior capsular reconstruction, lower trapezial tendon transfer, collagen bioinductive allograft augmentation), biceps tenodesis, or distal clavicle excision (type 2). Regarding postoperative follow-up visits, patients were routinely scheduled at 1, 3, 6 weeks, 3, 6, and 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical data included nature of concomitant procedures (ie, use of allograft, biceps tenodesis, capsular release), American Society of Anesthesiologists score (1 or 2 versus ≥3), number of anchors used, history of prior ipsilateral or contralateral nonarthroscopic shoulder surgery, prior ipsilateral or contralateral arthroscopic shoulder surgery, subsequent upper or lower extremity arthroscopy, and any ipsilateral revision surgery. The number of anchors placed was used as a surrogate for rotator cuff tear size based on the findings of Shah et al 21 Procedures were categorized as primary repair of the rotator cuff with or without decompression/débridement (type 1) versus those with concomitant use of allograft (superior capsular reconstruction, lower trapezial tendon transfer, collagen bioinductive allograft augmentation), biceps tenodesis, or distal clavicle excision (type 2). Regarding postoperative follow-up visits, patients were routinely scheduled at 1, 3, 6 weeks, 3, 6, and 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…11,16,17,21,26 Nevertheless, there has been an increasing trend in the use of knotless repair techniques over the past decade. 37 In cadaveric and animal studies, knotless transosseousequivalent repair demonstrated superior self-reinforcement (greater progression of footprint compression with increasing tendon loads) compared with medial knot repair. 33,38 In smaller tears ( 1.0 cm), single-row repair has demonstrated good success, but the suture pattern and anchor location influence tendon morphology and footprint re-creation.…”
mentioning
confidence: 99%